A new approach to the synthesis of heteroannulated 3,1-oxazin-4-ones from β-enamino esters and phosgeneiminium salts - Wang, Zhijun; Neidlein, Richard; Krieger, Claus (Synthesis, 2000)
The heterocyclic β-enamino ester, ethyl 3,4-diamino-6-(dimethylamino)thieno[2,3-d]pyrimidine-2-carboxylate (3) was reacted with phosgeneiminium salts 6a,b to yield 4H-pyrimido[5′,4′:4,5]thieno[3,2-d][1,3]oxazin-4-ones 7a,b, respectively. Similarly, the reaction of dichloromethylene dimethylammonium chloride 6a with o-aminothiophenecarboxylates 8 and 10 afforded the thienoxazinones 9 and 11. In the case of the o-aminopyrazolecarboxylate 12, the pyrazoloxazinone 13a was formed in low yield, while the ureidopyrazole 13b was the main product. Reaction of 6a with o-aminopyrazinecarboxylate 14 or o-aminoisoxazolecarboxylate 16 did not afford any bicyclic oxazinones were produced with 6a. Instead, the monocyclic products 15 and 17 were obtained.